Engineered cells as biosensing systems in biomedical analysis - Raut, Nilesh; O’Connor, Gregory; Pasini, Patrizia; Daunert, Sylvia (Analytical and bioanalytical chemistry, 2012)
Over the past two decades there have been great advances in biotechnology, including use of nucleic acids, proteins, and whole cells to develop a variety of molecular analytical tools for diagnostic, screening, and pharmaceutical applications. Through manipulation of bacterial plasmids and genomes, bacterial whole-cell sensing systems have been engineered that can serve as novel methods for analyte detection and characterization, and as more efficient and cost-effective alternatives to traditional analytical techniques. Bacterial cell-based sensing systems are typically sensitive, specific and selective, rapid, easy to use, low-cost, and amenable to multiplexing, high-throughput, and miniaturization for incorporation into portable devices. This critical review is intended to provide an overview of available bacterial whole-cell sensing systems for assessment of a variety of clinically relevant analytes. Specifically, we examine whole-cell sensing systems for detection of bacterial quorum sensing molecules, organic and inorganic toxic compounds, and drugs, and for screening of antibacterial compounds for identification of their mechanisms of action. Methods used in the design and development of whole-cell sensing systems are also reviewed.